Ultra-thin ceramic coating for battery separators

The ceramic-coated separator addresses the issues of electrical shorts and high costs by using a thin polymer substrate with ultra-thin ceramic layers, enhancing charging capacity and reducing manufacturing complexity.

JP7614087B2Active Publication Date: 2025-01-15APPLIED MATERIALS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021509775
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-08-21
Publication Date
2025-01-15
Estimated Expiration
2038-08-21

AI Technical Summary

Technical Problem

Current battery separators are susceptible to electrical shorts due to lithium dendrite formation, require complex manufacturing methods, and are costly, limiting the size, weight, and charging capacity of energy storage devices.

Method used

A ceramic-coated separator with a thin polymer substrate and ultra-thin ceramic layers on both sides, formed using PVD techniques, providing mechanical stability and ionic conductivity while preventing dendrite growth.

Benefits of technology

The ceramic-coated separator reduces thermal shrinkage and mechanical instability, enabling thinner separators with improved charging capacity and reduced manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007614087000001
    Figure 0007614087000001
  • Figure 0007614087000002
    Figure 0007614087000002
  • Figure 0007614087000003
    Figure 0007614087000003
Patent Text Reader

Abstract

A separator, a high-performance electrochemical device such as a battery or capacitor including the separator, and a system and method for manufacturing the same are provided. In one implementation, a separator is provided. The separator includes a polymer substrate (131) capable of conducting ions, having a first surface and a second surface opposite the first surface. The separator further includes a first ceramic-containing layer (136) capable of conducting ions formed on the first surface. The first ceramic-containing layer (136) has a thickness in the range of about 1,000 nanometers to about 5,000 nanometers. The separator further includes a second ceramic-containing layer (138) capable of conducting ions formed on the second surface. The second ceramic-containing layer (138) is a binder-free ceramic-containing layer and has a thickness in the range of about 1 nanometer to about 1,000 nanometers. [Selected Figure] Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Field Implementations of the present disclosure generally include separators, high performance electrochemical devices such as batteries and capacitors that include the separators, systems, and methods for making the same. [Background technology]

[0002] 2. Description of Related Art Fast-charging, high-capacity energy storage devices such as capacitors and lithium-ion (Li-ion) batteries are being used in an increasing number of applications, including portable electronics, medical, transportation, grid-connected bulk energy storage, renewable energy storage, and uninterruptible power supplies (UPS).

[0003] A Li-ion battery typically includes an anode electrode, a cathode electrode, and a separator disposed between the anode and cathode electrodes. The separator is an electronic insulator that provides physical and electrical isolation between the cathode and anode electrodes. The separator is typically made of microporous polyethylene and polyolefin. During electrochemical reactions, e.g., during charging and discharging, lithium ions are transported through the pores of the separator between the two electrodes, via the electrolyte. Thus, high porosity helps to increase ionic conductivity. However, some highly porous separators are susceptible to electrical shorting when lithium dendrites form, creating a short circuit between the electrodes during cycling.

[0004] Currently, battery cell manufacturers purchase separators in which the anode and cathode electrodes are laminated together in a separate processing step. Other separators are typically made by wet or dry extrusion of a polymer and stretching it to create holes (cracks) in the polymer material. Separators are typically one of the most expensive components in a Li-ion battery, accounting for more than 20% of the material cost of a battery cell.

[0005] In most energy storage applications, the charging time and charging capacity of an energy storage device are important parameters. In addition, the size, weight, and / or cost of such energy storage devices can be significant limitations. The use of currently available commercially available separators has a number of drawbacks: such commercially available materials limit the minimum size of the electrodes that can be constructed, are vulnerable to electrical shorts, and require complex manufacturing methods and expensive materials. Furthermore, current separator designs often suffer from the growth of lithium dendrites that can cause shorts.

[0006] Therefore, fast charging technologies require high capacity energy storage devices with separators that are small, lightweight, and can be more cost-effective to manufacture. Summary of the Invention

[0007] Implementations of the present disclosure generally include separators, high performance electrochemical devices, such as batteries and capacitors, including the separators, systems, and methods for their manufacture. In one implementation, a separator is provided. The separator includes a polymer substrate capable of conducting ions and has a first surface and a second surface opposite the first surface. The separator further includes a first ceramic-containing layer capable of conducting ions formed on the first surface. The first ceramic-containing layer has a thickness in the range of about 1,000 nanometers to about 5,000 nanometers. The separator further includes a second ceramic-containing layer capable of conducting ions formed on the second surface. The second ceramic-containing layer is a binder-free ceramic-containing layer and has a thickness in the range of about 1 nanometer to about 1,000 nanometers.

[0008] In another implementation, a battery is provided. The battery includes an anode containing at least one of lithium metal, lithium alloy, graphite, silicon-containing graphite, nickel, copper, tin, indium, silicon, or combinations thereof. The battery further includes a cathode. The battery further includes a separator disposed between the anode and the cathode. The separator includes a polymer substrate capable of conducting ions having a first surface and a second surface opposite the first surface. The separator further includes a first ceramic-containing layer capable of conducting ions formed on the first surface. The first ceramic-containing layer has a thickness in the range of about 1,000 nanometers to about 5,000 nanometers. The separator further includes a second ceramic-containing layer capable of conducting ions formed on the second surface. The second ceramic-containing layer is a binder-free ceramic-containing layer and has a thickness in the range of about 1 nanometer to about 1,000 nanometers.

[0009] In yet another implementation, a method of forming a separator for a battery is provided. The method includes exposing a material deposited on a microporous ion-conducting polymer layer positioned in a treatment region to an evaporation process. The microporous ion-conducting polymer layer has a first surface, a second surface opposite the first surface, and a first ceramic-containing layer capable of conducting ions formed on the first surface. The first ceramic-containing layer has a thickness in a range from about 1,000 nanometers to about 5,000 nanometers. The method further includes reacting the evaporated material with a reactive gas and / or plasma to deposit a second ceramic-containing layer capable of conducting ions on the second surface of the microporous ion-conducting polymer layer. The second ceramic-containing layer is a binder-free ceramic-containing layer and has a thickness in a range from about 1 nanometer to about 1,000 nanometers.

[0010] In yet another implementation, a method of forming a separator for a battery is provided. The method includes exposing a first material deposited on a microporous ion-conducting polymer layer positioned in a treatment region to an evaporation process. The microporous ion-conducting polymer layer has a first surface, a second surface opposite the first surface, and a first ceramic-containing layer capable of conducting ions formed on the first surface. The first ceramic-containing layer has a thickness in a range of about 1,000 nanometers to about 5,000 nanometers. The method further includes reacting the evaporated first material with a reactive gas and / or plasma to deposit a second ceramic-containing layer capable of conducting ions on the second surface of the microporous ion-conducting polymer layer. The second ceramic-containing layer is a binder-free ceramic-containing layer and has a thickness in a range of about 1 nanometer to about 100 nanometers. The method further includes exposing the microporous ion-conducting polymer layer to a first cooling process. The method further includes reacting the vaporized second material with a reactive gas and / or plasma to deposit a third ceramic-containing layer capable of conducting ions on the second ceramic-containing layer, The third ceramic-containing layer is a binder-free ceramic-containing layer and has a thickness in a range from about 1 nanometer to about 100 nanometers.

[0011] In order that the above-mentioned features of the present disclosure may be understood in detail, a more detailed description of the implementations briefly summarized above can be obtained by referring to the implementations. Some of the implementations are illustrated in the accompanying drawings. However, it should be noted that the accompanying drawings illustrate only typical implementations of the present disclosure, since the present disclosure may admit of other equally effective implementations, and therefore should not be considered as limiting the scope of the present invention. [Brief description of the drawings]

[0012] [Figure 1] 1 illustrates a cross-sectional view of one implementation of a cell structure formed in accordance with one or more implementations described herein. [Diagram 2]1 illustrates a cross-sectional view of a ceramic coated separator formed in accordance with one or more implementations described herein. [Diagram 3] 1 shows a process flow diagram summarizing one implementation of a method for forming an electrode structure according to implementations described herein. [Figure 4] FIG. 1A shows a cross-sectional view of another ceramic coated separator formed in accordance with one or more implementations described herein, and FIG. 1B shows an exploded cross-sectional view of a portion of the ceramic coated separator shown in FIG. [Diagram 5] 1 shows a process flow diagram summarizing one implementation of another method for forming a ceramic coated separator according to implementations described herein. [Figure 6] A shows a schematic top view of an evaporator for forming a ceramic coated separator according to an implementation described herein, B shows a schematic front view of the evaporator shown in A, and C shows a schematic top view of the evaporator shown in A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] For ease of understanding, wherever possible, identical reference numerals have been used to designate identical elements that are common to multiple figures. It is contemplated that elements and features of one implementation may be beneficially incorporated in other implementations without further recitation.

[0014] The following disclosure describes separators, high performance electrochemical cells and batteries including the separators, systems, and methods for manufacturing the same. Specific details are presented in the following description and in Figures 1 to 6C to provide a thorough understanding of various implementations of the present disclosure. Other details describing well-known structures and systems related to electrochemical cells and batteries are often not presented in the following disclosure so as not to unnecessarily obscure the description of the various implementations.

[0015] Many of the details, dimensions, angles, and other features shown in the drawings are merely illustrative of specific implementations. Thus, other implementations can have other details, components, dimensions, angles, and features without departing from the spirit or scope of the present disclosure. In addition, further implementations of the present disclosure can be practiced without including some of the details described below.

[0016] The implementations described herein are based on TopMet TM , SmartWeb TM , TopBeam TM The rapid evaporation process is described below with reference to a roll-to-roll coating system that may be performed using a roll-to-roll coating system such as the EPSON 1010226, all of which are available from Applied Materials, Inc., Santa Clara, Calif. Other tools capable of performing rapid evaporation processes may also be adapted to take advantage of the implementations described herein. In addition, any system that allows for the rapid evaporation process described herein may be used to advantage. The apparatus descriptions described herein are exemplary and should not be understood or construed as limiting the scope of the implementations described herein. Although described as a roll-to-roll process, it should be understood that the implementations described herein may be performed on individual polymer substrates.

[0017] Currently available battery generations, especially Li-ion batteries, use porous polymer separators. These are susceptible to thermal shrinkage and can lead to short circuits between the positive and negative electrodes or the corresponding current collectors. A ceramic coating on the separator helps to inhibit direct contact between the electrodes and also helps to prevent potential dendrite growth associated with lithium metal. Current state-of-the-art ceramic coatings are performed using wet coating (e.g., slot die technology) of ceramic particles dispersed in a polymer binder to create a composite, and a solvent is used to create a slurry. The thickness of the ceramic coating is typically around 3 microns and includes randomly oriented dielectric material bound by a polymer resulting in a random pore structure. Existing ceramic particle coating methods have difficulty reducing the twisting due to this random orientation of the ceramic particles. Furthermore, it is difficult to reduce the thickness of current ceramic coatings using current wet coating methods. To compensate for the increased surface area of ​​the fine ceramic powder particles, current wet coating methods include increasing the amount of both binder and solvent, which reduces the viscosity of the slurry. Thus, current wet coating methods suffer from multiple problems.

[0018] From a manufacturing standpoint, dry-processed ceramic coatings are ideal from a cost and performance standpoint. However, dry processes such as physical vapor deposition (PVD) are performed at high processing temperatures. The combination of reduced thickness of the polymer separator and high processing temperatures results in heat-induced damage, such as melting or wrinkling in the polymer separator. In addition, thinner polymer separators often lack the mechanical integrity for current roll-to-roll processing systems.

[0019] In the present disclosure, a thin polymer separator stack is provided. The thin polymer separator stack includes an ultra-thin ceramic coating formed on a first side of the front side of the thin polymer separator, which inhibits thermal shrinkage while maintaining a desired ionic conductivity. The ultra-thin ceramic coating can be deposited using PVD techniques at high temperatures. The ultra-thin ceramic coating can have a thickness in the range of about 0.05 to about 0.5 microns. The thin polymer separator stack further includes a thick ceramic coating formed on a second side or back side of the thin polymer separator, which provides mechanical stability while maintaining a desired ionic conductivity. The thick ceramic coating can be deposited using wet coating techniques. The thick ceramic coating can have a thickness in the range of about 1 micron to about 5 microns. Thus, the thin polymer separator stack includes the advantages of reduced thermal shrinkage due to improved mechanical stability while maintaining a desired ionic conductivity at a reduced separator thickness (e.g., 12 microns or less).

[0020] FIG. 1 illustrates an example of a cell structure 100 having a ceramic coated separator according to an implementation of the present disclosure. The cell structure 100 includes a positive current collector 110, a positive electrode 120, a ceramic coated separator 130, a negative electrode 140, and a negative current collector 150. It should be noted that while the current collector in FIG. 1 extends beyond the stack, the current collector need not extend beyond the stack, and the portion that extends beyond the stack may be used as a tab. Although the cell structure 100 is shown as a planar structure, it may be formed into a cylindrical shape by rolling a stack of layers, and other cell configurations (e.g., prismatic cells, button cells) may be formed.

[0021] The current collectors 110, 150 on the positive electrode 120 and the negative electrode 140, respectively, can be the same or different electronic conductors. Examples of metals that can comprise the current collectors 110, 150 include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), tin (Sn), silicon (Si), manganese (Mn), magnesium (Mg), alloys thereof, and combinations thereof. In one implementation, the current collector 110 includes aluminum and the current collector 150 includes copper.

[0022] The negative electrode 140 or anode may be any material compatible with the positive electrode 120. The negative electrode 140 may have an energy capacity of 372 mAh / g or greater, preferably ≧700 mAh / g, and most preferably ≧1,000 mAh / g. The negative electrode 140 may be constructed from graphite, silicon-containing graphite (e.g., silicon (<5%) blended graphite), lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy), or mixtures of lithium metal and / or lithium alloy with materials such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, oxides thereof, or combinations thereof.

[0023] The positive electrode 120, or cathode, may be any material compatible with the anode and may include an intercalation compound, an insertion compound, or an electrochemically active polymer. Examples of suitable intercalation materials include, for example, lithium-containing metal oxides, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, VO 13 and V2O5. Suitable lithium-containing oxides include layered, such as lithium cobalt oxide (LiCoO2), or mixed metal oxides, such as LiNiCoO 1-2x MnO2, LiNiMnCoO2 (“NMC”), LiNi 0.5 Mn 1.5 O4, Li(Ni 0.8 Co 0.15 Al 0.05)O2, LiMn2O4, and doped lithium-rich layered materials (x is a zero or non-zero number). Suitable phosphates include iron olivine (LiFePO4), and its variants (LiFe (1-x) Mg x PO4, etc.), LiMoPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiVOPO4, LiMP2O7, or LiFe 1.5 P2O7, where x is zero or a non-zero number. Suitable fluorophosphates include LiVPO4F, LiAlPO4F, Li5V(PO4)2F2, Li5Cr(PO4)2F2, Li2CoPO4F, or Li2NiPO4F. Suitable silicates may be Li2FeSiO4, Li2MnSiO4, or Li2VOSiO4. An exemplary non-lithium compound is Na5V2(PO4)2F3.

[0024] The electrolytes injected into the cell components 120, 130, and 140 may be composed of liquid / gel or solid polymers and may be different from each other. Any suitable electrolyte may be used. In some implementations, the electrolyte mainly includes a salt and a medium (e.g., in a liquid electrolyte, the medium may also be called a solvent, and in a gel electrolyte, the medium may be a polymer matrix). The salt may be a lithium salt. The lithium salt may include, for example, LiPF6, LiAsF6, LiCF3SO3, LiN(CF3SO3)3, LiBF6, and LiClO4, BETTE electrolyte (commercially available from 3M Company, Minneapolis, Minnesota), and combinations thereof.

[0025] 2 illustrates a cross-sectional view of a ceramic-coated separator 130 formed in accordance with one or more implementations described herein. The ceramic-coated separator 130 includes a porous (e.g., microporous) polymer substrate 131 (e.g., a separator film) capable of conducting ions. The porous polymer substrate 131 has a first surface 132 and a second surface 134 opposite the first surface 132. A first ceramic-containing layer 136 capable of conducting ions is formed on at least a portion of the first surface 132 of the porous polymer substrate 131. A second ceramic-containing layer 138 (e.g., an ultra-thin ceramic coating) capable of conducting ions is formed on at least a portion of the second surface 134 of the porous polymer substrate 131. The first ceramic-containing layer 136 has a thickness greater than a thickness of the second ceramic-containing layer 138.

[0026] In some implementations, the porous polymer substrate 131 does not need to be ionically conductive, but after being filled with an electrolyte (such as a liquid, gel, solid, or a combination thereof), the combination of the porous substrate and electrolyte is ionically conductive. The first ceramic-containing layer 136 and the second ceramic-containing layer 138 are adapted to at least prevent electronic shorting (e.g., direct or physical contact between the anode and cathode) and block dendrite growth. The porous polymer substrate 131 may be adapted to at least block (or shut down) ionic conductivity (or flow) between the anode and cathode during a thermal runaway event. The first ceramic-containing layer 136 and the second ceramic-containing layer 138 of the ceramic coating separator 130 should be sufficiently conductive to allow ionic flow between the anode and cathode such that the cell structure 100 generates a desired amount of current. As described herein, in one implementation, the second ceramic-containing layer 138 is formed on the porous polymer substrate 131 using an evaporation technique.

[0027] In one implementation, the porous polymer substrate 131 is a microporous ion-conducting polymer substrate. In one implementation, the porous polymer substrate is a multi-layer polymer substrate. In some implementations, the porous polymer substrate 131 is made of any commercially available polymer microporous membrane (e.g., single or multi-layer). For example, Polypore (Celgard, Charlotte, NC), Toray Tonen (battery separator film (BSF)), SK Energy (lithium ion battery separator (LiBS)), Evonik Industries (SEPARION® ceramic separator membrane), Asahi Kasei (Hipore TM Polyolefin flat film membranes), products manufactured by DuPont (Energain®). In some implementations, the porous polymer substrate 131 has a porosity in the range of 20 to 80% (e.g., in the range of 28 to 60%). In some implementations, the porous polymer substrate 131 has an average pore size in the range of 0.02 to 5 microns (e.g., 0.08 to 2 microns). In some implementations, the porous polymer substrate 131 has a Gurley number in the range of 15 to 150 seconds (Gurley number refers to the time it takes for 10 cc of air to pass through a 1 square inch membrane in 12.2 inches of water). In some implementations, the porous polymer substrate 131 comprises a polyolefin polymer. Examples of suitable polyolefin polymers include polypropylene, polyethylene, or a combination thereof. In some implementations, the porous polymer substrate 131 is a polyolefin membrane. In some implementations, the polyolefin membrane is a polyethylene membrane or a polypropylene membrane.

[0028] In one implementation, the porous polymer substrate 131 has a thickness "T1" in the range of about 1 micron to about 50 microns, for example, in the range of about 3 microns to about 25 microns, in the range of about 7 microns to about 12 microns, or in the range of about 14 microns to about 18 microns.

[0029] The first ceramic-containing layer 136 provides mechanical support for the porous polymer substrate 131. The inventors have found that the inclusion of the first ceramic-containing layer 136 reduces thermal shrinkage of the porous polymer substrate 131 during processing at high temperatures. Thus, the inclusion of the first ceramic-containing layer 136 allows for thinner separator materials to be processed at high temperatures.

[0030] The first ceramic-containing layer 136 includes one or more ceramic materials. The ceramic material may be an oxide. In one implementation, the first ceramic-containing layer 136 includes a ceramic material such as aluminum oxide (Al2O3), AlO x, AlOxNy, AlN (aluminum deposited in a nitrogen environment), aluminum hydroxide ((AlO(OH)) (e.g., diaspore (α-AlO(OH))), boehmite (γ-AlO(OH)), or acadalite (5Al2O3·H2O)), calcium carbonate (CaCO3), titanium dioxide (TiO2), SiS2, SiPO4, silicon oxide (SiO2), zirconium oxide (ZrO2), hafnium oxide (HfO2), MgO, TiO2, Ta2O5, Nb2O5, LiAlO2, BaTiO3, BN, ion conducting garnets, ion conducting perovskites, ion conducting antiperovskites, porous glass ceramics, and the like, and combinations thereof. In one implementation, the first ceramic-containing layer 136 comprises a combination of AlOx and Al2O3. In one implementation, the first ceramic-containing layer 136 comprises a material selected from the group including, consisting of, or consisting essentially of porous aluminum oxide, porous ZrO2, porous HfO2, porous SiO2, porous MgO, porous TiO2, porous Ta2O5, porous Nb2O5, porous LiAlO2, porous BaTiO3, ion-conducting garnets, anti-ion-conducting perovskites, porous glass dielectrics, or combinations thereof. In one implementation, the first ceramic-containing layer 136 comprises a binder material. In some implementations, the first ceramic-containing layer 136 is a porous aluminum oxide layer. The first ceramic-containing layer 136 can be formed using any suitable deposition technique that achieves the desired ion conductivity, mechanical integrity, and thickness of the first ceramic-containing layer 136. Suitable techniques include slurry deposition techniques or wet coating techniques such as slot-die and doctor blade techniques. In one implementation, the first ceramic-containing layer 136 is deposited using ceramic particles dispersed in a polymer binder to create a composite and a solvent to create a slurry. In one implementation, the first ceramic-containing layer 136 and the porous polymer substrate 131 are pre-fabricated and supplied together.

[0031] In one implementation, the first ceramic-containing layer 136 has a thickness "T2" in the range from about 1,000 nanometers to about 5,000 nanometers, such as in the range from about 1,000 nanometers to about 3,000 nanometers, or in the range from about 1,000 nanometers to about 2,000 nanometers.

[0032] The second ceramic-containing layer 138 includes one or more ceramic materials. The ceramic material may be an oxide. In one implementation, the second ceramic-containing layer 138 includes a ceramic material such as aluminum oxide (Al2O3), AlO x , AlOxNy, AlN (aluminum deposited in a nitrogen environment), aluminum hydroxide ((AlO(OH)) (e.g., diaspore (α-AlO(OH))), boehmite (γ-AlO(OH)), or acadalite (5Al2O3·H2O)), calcium carbonate (CaCO3), titanium dioxide (TiO2), SiS2, SiPO4, silicon oxide (SiO2), zirconium oxide (ZrO2), hafnium oxide (HfO2), MgO, TiO2, Ta2O5, Nb2O5, LiAlO2, BaTiO3, BN, ion conducting garnets, ion conducting perovskites, ion conducting antiperovskites, porous glass ceramics, and the like, and combinations thereof. In one implementation, the first ceramic-containing layer 136 comprises a combination of AlOx and Al2O3. In one implementation, the second ceramic-containing layer 138 comprises a material selected from the group including, consisting of, or consisting essentially of porous aluminum oxide, porous ZrO2, porous HfO2, porous SiO2, porous MgO, porous TiO2, porous Ta2O5, porous Nb2O5, porous LiAlO2, porous BaTiO3, ion-conducting garnets, anti-ion-conducting perovskites, porous glass dielectrics, or combinations thereof. The second ceramic-containing layer 138 is a binder-free dielectric layer. In some implementations, the second ceramic-containing layer 138 is a porous aluminum oxide layer. The second ceramic-containing layer 138 is typically deposited using evaporation techniques described herein.

[0033] In one implementation, the second ceramic-containing layer 138 has a thickness "T3" in the range from about 1 nanometer to about 1,000 nanometers, such as in the range from about 50 nanometers to about 500 nanometers, or in the range from about 50 nanometers to about 200 nanometers.

[0034] In some implementations, the second ceramic-containing layer 138 includes a plurality of dielectric pillars. The dielectric pillars can have a diameter that extends from the base of the pillar (e.g., where the pillar contacts the porous substrate) to the top of the pillar. The dielectric pillars typically include dielectric particulates. Nanostructured contours or channels are typically formed between the dielectric particulates.

[0035] In some implementations, the second ceramic-containing layer 138 can include one or more of various forms of porosity. In some implementations, the posts of the second ceramic-containing layer 138 form a nanoporous structure between the posts of ceramic material. In one implementation, the nanoporous structure can have a plurality of nanopores sized to have an average pore size or diameter of less than about 10 nanometers (e.g., about 1 nanometer to about 10 nanometers, about 3 nanometers to 5 nanometers). In another implementation, the nanoporous structure can have a plurality of nanopores sized to have an average pore size or diameter of less than about 5 nanometers. In one implementation, the nanoporous structure has a plurality of nanopores with a diameter in the range of about 1 nanometer to about 20 nanometers (e.g., about 2 nanometers to about 15 nanometers, or about 5 nanometers to about 10 nanometers). The nanoporous structure provides a significant increase in the surface area of ​​the second ceramic-containing layer 138. The pores of the nanoporous structure can act as liquid electrolyte reservoirs and provide extra surface area for ionic conduction.

[0036] In one implementation, the first ceramic-containing layer 136 and the second ceramic-containing layer 138 comprise the same ceramic material. In another implementation, the first ceramic-containing layer 136 and the second ceramic-containing layer 138 comprise different ceramic materials.

[0037] 3 is a process flow diagram summarizing one implementation of a method 300 for forming a ceramic coated separator according to implementations described herein. The ceramic coated separator may be the ceramic coated separator 130 shown in FIGS. 1 and 2.

[0038] In step 310, a porous polymer substrate, e.g., porous polymer substrate 131, is provided having a first ceramic-containing layer, e.g., first ceramic-containing layer 136, formed on a first surface, e.g., first surface 132, of the porous polymer substrate. In one implementation, the first ceramic-containing layer 136 formed on the porous polymer substrate 131 is pre-fabricated and supplied together. In another implementation, the first ceramic-containing layer 136 is formed on the porous polymer substrate 131 using a slurry deposition process.

[0039] In step 320, the porous polymer substrate 131 with the first ceramic-containing layer 136 formed thereon is optionally subjected to a cooling process. In one implementation, the porous polymer substrate 131 can be cooled to a temperature between -20°C and room temperature (i.e., 20 to 22°C) (e.g., -10°C to 0°C). In some implementations, the porous polymer substrate 131 can be cooled by cooling the processing drum over which the microporous ion-conducting polymer substrate moves during processing. Other active cooling means may be used to cool the microporous ion-conducting polymer substrate. During the evaporation process, the porous polymer substrate 131 can be exposed to temperatures in excess of 1,000°C, and therefore it is advantageous to cool the porous polymer substrate 131 prior to the evaporation process of step 330.

[0040] In step 330, the material to be deposited on the second surface of the porous polymer substrate 131 is exposed to an evaporation process that evaporates the material to be deposited in the treatment region. In one implementation, the material to be evaporated is a metal or a metal oxide. In one implementation, the material to be evaporated is selected from the group of aluminum (Al), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), titanium (Ti), yttrium (Y), lanthanum (La), silicon (Si), boron (B), silver (Ag), chromium (Cr), copper (Cu), indium (In), iron (Fe), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), nickel (Ni), tin (Sn), ytterbium (Yb), lithium (Li), calcium (Ca), or combinations thereof. In another implementation, the evaporated material is selected from the group of zirconium oxide, hafnium oxide, silicon oxide, magnesium oxide, titanium oxide, tantalum oxide, niobium oxide, lithium aluminum oxide, barium titanium oxide, or combinations thereof. In one implementation, the deposited material is a metal, such as aluminum. Furthermore, the evaporated material may be an alloy of two or more metals. The evaporated material is a material that evaporates during evaporation, by which the microporous ion-conducting polymer substrate is coated. The deposited material (e.g., aluminum) can be provided in a crucible. The deposited material can be evaporated, for example, by thermal evaporation or electron beam evaporation techniques. In another implementation, the deposited material is deposited using chemical vapor deposition (CVD) or atomic layer deposition (ALD) techniques. For example, in one implementation, the deposited material is Al2O3 deposited by an ALD process. In another example, the deposited material is SiO2 deposited by a CVD process.

[0041] In some implementations, the material to be evaporated is fed to the crucible as a wire. In this case, the feed rate and / or the diameter of the wire must be selected to achieve the desired ratio of evaporated material to reactive gas. In some implementations, the diameter of the feed wire for feeding the crucible is selected between 0.5 mm and 2.0 mm (e.g., between 1.0 mm and 1.5 mm). These dimensions refer to a plurality of feed wires made of the evaporated material. In one implementation, the feed rate of the wire is between 50 cm / min and 150 cm / min (e.g., between 70 cm / min and 100 cm / min).

[0042] The crucible is heated to generate vapor, which reacts with the reactive gas and / or plasma provided in step 340 to coat the second surface 134 of the porous polymer substrate 131 with a second ceramic-containing layer, e.g., second ceramic-containing layer 138. Typically, the crucible is heated by applying a voltage to the electrodes of the crucible, which are positioned on either side of the crucible. Generally, according to the implementations described herein, the material of the crucible is electrically conductive. Typically, the material used as the material of the crucible is temperature resistant up to the temperature used for melting and evaporation. Typically, the crucible of the present disclosure is made of one or more materials selected from the group including, consisting of, or consisting essentially of metal borides, metal nitrides, metal carbides, non-metal borides, non-metal nitrides, non-metal carbides, nitrides, titanium nitrides, borides, graphite, TiB2, BN, B4C, and SiC.

[0043] The material to be deposited is melted and evaporated by heating the evaporation crucible. Heating can be achieved by providing a power source (not shown) connected to a first electrical connection and a second electrical connection of the crucible. For example, these electrical connections can be electrodes made of copper or an alloy thereof. Heating is thereby achieved by a current flowing through the body of the crucible. According to other implementations, heating can also be performed by a radiant heater of the evaporation device or an inductive heating unit of the evaporation device.

[0044] In some implementations, the evaporation unit can typically be heated to a temperature of 1,300°C to 1,600°C, for example 1,560°C. This is done by appropriately adjusting the current through the crucible or by appropriately adjusting the radiation. Typically, the crucible material is selected such that its stability is not adversely affected by temperatures in such range. Typically, the speed of the porous polymer substrate 131 is in the range of 20 cm / min to 200 cm / min, more typically in the range of 80 cm / min to 120 cm / min, for example 100 cm / min. In such cases, the means for transport must be capable of transporting the substrate at such a speed.

[0045] Optionally, in step 340, the evaporated material is reacted with a reactive gas and / or plasma to form a second ceramic-containing layer, e.g., second ceramic-containing layer 138, on a second surface of the porous polymer substrate, e.g., second surface 134. According to some implementations that can be combined with other implementations described herein, the reactive gas can be selected from the group including, consisting of, or consisting essentially of an oxygen-containing gas, a nitrogen-containing gas, or combinations thereof. Examples of oxygen-containing gases that can be used in the implementations described herein include oxygen (O), ozone (O), oxygen radicals (O), and nitrogen-containing gases. * ), or a combination thereof. Examples of nitrogen-containing gases that can be used in the implementations described herein include N2, N2O, NO2, NH3, or a combination thereof. According to some implementations, an additional gas, typically an inert gas such as argon, can be added to the gas mixture containing the reactive gas, so that the amount of the reactive gas can be more easily controlled. According to some implementations, which can be combined with other implementations, the process can be performed in a 1 * 10 -2 mbar to 1 * 10 -6 mbar (e.g., 1 * 10 -3 mbar or less, 1 * 10 -4The method can be carried out in a vacuum environment with typical pressures of 1000 psi (0.2 psi or less).

[0046] In some implementations of reacting the evaporated material with a plasma, the plasma is an oxygen-containing plasma. In one implementation, the oxygen-containing plasma is formed from an oxygen-containing gas and optionally an inert gas. The oxygen-containing gas can be selected from the group of N2O, O2, O3, H2O, and combinations thereof. The optional inert gas can be selected from the group of helium, argon, or combinations thereof. In one implementation, the oxygen-containing plasma is formed by a remote plasma source and delivered to the processing region to react with the evaporated material to form the second ceramic-containing layer. In another implementation, the oxygen-containing plasma is formed in situ in the processing region and reacts with the evaporated material in the processing region to form the second ceramic-containing layer.

[0047] In some implementations, the evaporated material is deposited directly onto a second surface of the porous polymer substrate, e.g., second surface 134, to form a second ceramic-containing layer, e.g., second ceramic-containing layer 138. For example, in some implementations where the evaporated material is a metal oxide, the deposited material is deposited onto second surface 134 without the optional reactive gas / plasma treatment of step 340.

[0048] In step 350, optional post-deposition treatment of the deposited dielectric layer is performed. Optional post-deposition treatment may include a post-deposition plasma treatment to densify the deposited dielectric layer, for example to perform additional "functionalization" processes such as complete oxidation of AlOx to form Al2O3, or deposition of a polymeric material to increase the puncture resistance of the film.

[0049] FIG. 4A shows a cross-sectional view of another ceramic-coated separator 430 formed in accordance with one or more implementations described herein. FIG. 4B shows an exploded cross-sectional view of a portion of the ceramic-coated separator 430 shown in FIG. 4A. FIG. 5 is a process flow diagram summarizing one implementation of another method 500 for forming an electrode structure in accordance with implementations described herein. The method 500 corresponds to the manufacture of the ceramic-coated separator 430 shown in FIGS. 4A and 4B. The ceramic-coated separator 430 is similar to the ceramic-coated separator 130, except that the ceramic-coated separator 430 has a second ceramic-containing layer 438 formed by a multi-pass process.

[0050] In step 510, a porous polymer substrate, e.g., porous polymer substrate 131, is provided having a first ceramic-containing layer, e.g., first ceramic-containing layer 136, formed on a first surface, e.g., first surface 132, of the porous polymer substrate.

[0051] In step 520, the porous polymer substrate 131 is optionally subjected to a cooling process. In one implementation, the porous polymer substrate 131 can be cooled to a temperature between -20°C and room temperature (i.e., 20 to 22°C) (e.g., -10°C to 0°C). In some implementations, the porous polymer substrate 131 can be cooled by cooling the processing drum over which the microporous ion-conducting polymer substrate moves during processing. Other active cooling means may be used to cool the microporous ion-conducting polymer substrate. During the evaporation process, the porous polymer substrate 131 can be exposed to temperatures in excess of 1,000°C, and therefore it is advantageous to cool the porous polymer substrate 131 prior to the evaporation process of step 330.

[0052] In step 530, a first portion 440a of the second ceramic-containing layer 438 is formed on the second surface 134 of the porous polymer substrate. The first portion 440a of the second ceramic-containing layer 438 is formed by an evaporation process, as described in steps 330 and / or 340 of FIG. 3. The first portion 440a can include any of the ceramic materials disclosed herein. In one implementation, the first portion 440a has a thickness in a range from about 1 nanometer to about 50 nanometers, e.g., in a range from about 15 nanometers to about 50 nanometers, or in a range from about 20 nanometers to about 30 nanometers.

[0053] In step 540, the porous polymer substrate 131 having the first portion 440a of the second ceramic-containing layer 438 is optionally exposed to a cooling process. The cooling process of step 540 can be performed similarly to the cooling process of step 520.

[0054] In step 550, the second portion 440b of the second ceramic-containing layer 438 is formed on the first portion 440a of the second ceramic-containing layer 438. The second portion 440b of the second ceramic-containing layer 438 is formed by an evaporation process, as described in steps 330 and 340 of FIG. 3. The second portion 440b can include any of the ceramic materials disclosed herein. In one implementation, the second portion 440b has a thickness in the range of about 1 nanometer to about 50 nanometers, e.g., in the range of about 15 nanometers to about 50 nanometers, or in the range of about 20 nanometers to about 30 nanometers.

[0055] In step 560, the porous polymer substrate 131 having the first portion 440a and the second portion 440b of the second ceramic-containing layer 438 is optionally exposed to a cooling process. The cooling process of step 560 can be performed similarly to the cooling processes of steps 520 and 530.

[0056] At step 570, a third portion 440c of the second ceramic-containing layer 438 is formed on the second portion 440b of the second ceramic-containing layer 438. The third portion 440c of the second ceramic-containing layer 438 is formed by an evaporation process, as described in steps 330 and 340 of FIG. 3. The third portion 440c may include any of the ceramic materials disclosed herein. In one implementation, the third portion 440c has a thickness in a range from about 1 nanometer to about 50 nanometers, such as in a range from about 15 nanometers to about 50 nanometers, or in a range from about 20 nanometers to about 30 nanometers.

[0057] In one implementation, the first portion 440a, the second portion 440b, and the third portion 440c include the same or similar ceramic material. For example, the first portion 440a, the second portion 440b, and the third portion 440c include porous AlO x In another implementation, at least two of the first portion 440a, the second portion 440b, and the third portion 440c include different ceramic materials. For example, the first portion 440a includes porous AlO x 4B, three layers 440a-c are shown in FIG. 4B.

[0058] FIG. 6A shows a schematic top view of an evaporation apparatus 600 for forming a ceramic-coated separator according to an implementation described herein. FIG. 6B shows a schematic front view of the evaporation apparatus shown in FIG. 6A. FIG. 6C shows a schematic top view of the evaporation apparatus 600 shown in FIG. 6A. The evaporation apparatus 600 can be used to form a ceramic-coated separator described herein. The evaporation apparatus 600 can be used to perform the method 300 and the method 500 described herein. For example, the evaporation apparatus can be used to deposit an ultra-thin ceramic coating, e.g., the second ceramic-containing layer 138, on a conductive flexible substrate, e.g., a porous polymer substrate 131, having a thicker ceramic-containing layer 636, e.g., the first ceramic-containing layer 136, formed thereon.

[0059] 6A and 6B, an evaporation apparatus 600 includes a first set 610 of evaporation crucibles aligned in a first line 620 along a first direction, e.g., along the x-direction shown in FIG. 6A, to generate a cloud 651 of evaporation material deposited on a flexible substrate 660. In one implementation, the flexible substrate 660 includes a porous polymer substrate 631, e.g., porous polymer substrate 131, on which a thick ceramic-containing layer 636, e.g., first ceramic-containing layer 136, is formed.

[0060] Referring to FIG. 1 as an example, typically, the flexible substrate 660 moves in the y-direction during the deposition process. The first set of evaporation crucibles 610 shown in FIG. 6A includes crucibles 611 to 617. Furthermore, as exemplarily shown in FIG. 6C, the evaporation apparatus 600 includes a gas supply pipe 630 extending in a first direction and disposed between the first set of evaporation crucibles 610 and the processing drum 670. As shown in FIG. 6C, typically, the gas supply pipe 630 includes a plurality of outlets 633 for providing gas supply directed into the evaporated material cloud 651. Furthermore, as shown by the two arrows in FIG. 6B, the evaporation apparatus is configured such that the position of the plurality of outlets is adjustable to change the position of the gas supply directed into the evaporated material cloud 651.

[0061] It should be understood that the evaporation apparatus 600 described herein may therefore be an evaporation apparatus for a reactive evaporation process. In some implementations, the crucibles described herein may be adapted to provide a material to be evaporated onto a substrate to be coated. For example, the crucible may provide one component of a material to be deposited as a layer on a substrate. In particular, the crucibles described herein may include a metal, such as aluminum, that is evaporated within the crucible. Furthermore, the material evaporated from the crucible may react with additional components, such as reactive gases, such as oxygen, and / or plasmas, such as oxygen-containing plasmas, in an evaporation apparatus to form a ceramic-containing layer on a flexible substrate as described herein. Thus, the aluminum from the crucible, together with the oxygen and / or oxygen-containing plasma described herein, may form a layer of AlOx, Al2O3, and / or Al2O3 / AlO3 on the flexible substrate in an evaporation apparatus according to an implementation described herein. x In view of the implementations described herein, one skilled in the art will appreciate that any material, particularly any metal, may be used as the material in the crucible, as long as the vapor pressure of the material can be achieved by thermal evaporation.

[0062] During processing, the flexible substrate 660 is exposed to the material evaporated by the set of crucibles 610, as exemplarily shown in Fig. 6B, indicated by a cloud 651 of evaporated material. Furthermore, during processing, a gas supply and / or plasma is directed into the cloud 651 of evaporated material, such that a portion of the evaporated material can react with the supplied gas and / or plasma. Thus, the flexible substrate 660 is further exposed to the evaporated material reacted with the supplied gas and / or plasma, so that during processing the flexible substrate 660 is coated with a layer comprising the material evaporated by the crucibles and the supplied gas and / or plasma, for example in the form of a reaction product of the components supplied by the crucibles and the gas supply pipes.

[0063] In summary, some of the advantages of the present disclosure include the efficient formation of a thin polymer separator stack. The thin polymer separator stack includes an ultra-thin ceramic coating formed on a first side, the front side, of the thin polymer separator, which inhibits thermal shrinkage while maintaining a desired ionic conductivity. The ultra-thin ceramic coating can be deposited using PVD techniques at high temperatures. The thin polymer separator stack further includes a thick ceramic coating formed on a second side or back side of the thin polymer separator, which provides mechanical stability while maintaining a desired ionic conductivity. Thus, the thin polymer separator stack includes the advantages of reduced thermal shrinkage due to improved mechanical stability while maintaining a desired ionic conductivity at reduced separator thickness (e.g., 12 microns or less).

[0064] When introducing elements of the present disclosure or example aspect or implementation(s) thereof, the articles "a," "an," and "the" and "said" mean that there are one or more of the elements.

[0065] The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements.

[0066] The term "about" generally indicates within ±0.5%, 1%, 2%, 5%, or up to ±10% of the indicated value. For example, a pore size of about 10 nm generally indicates within 10 nm ±10% in the broadest sense, i.e., 9.0-11.0 nm. Additionally, the term "about" can indicate measurement error (i.e., limitations of the measurement method) or, alternatively, the variation or average of a physical property of a group (e.g., a population of pores).

[0067] The term "crucible" as used herein is to be understood as a unit that, when heated, is capable of evaporating the material fed into it. In other words, a crucible is defined as a unit adapted to convert a solid material into vapor. Within the scope of the present disclosure, the terms "crucible" and "evaporation unit" are used synonymously.

[0068] The term "processing drum" as used herein should be understood as a roller used during the processing of a flexible substrate as described herein. In particular, a "processing drum" is understood as a roller configured to support a flexible substrate during processing. More particularly, the processing drums described herein may be arranged and configured such that a flexible substrate, e.g., a foil or a web, is wrapped around at least a portion of the processing drum. For example, during processing, typically, the flexible substrate is in contact with at least a lower portion of the processing drum. In other words, during processing, the flexible substrate is wrapped around the processing drum such that the flexible substrate contacts the lower portion of the processing drum and the flexible substrate is disposed on the lower portion of the processing drum.

[0069] The term "gas supply pipe" is understood as a pipe arranged and configured to provide a gas supply to the evaporation crucible, in particular to the space between a set of evaporation crucibles and the processing drum. For example, the gas supply pipe can be positioned and / or shaped to direct the gas supply into the cloud of evaporated material between the first set of evaporation crucibles and the processing drum. Typically, the gas supply pipe includes an opening or outlet arranged and configured to be able to direct the gas supply from the gas supply pipe into the cloud of evaporated material. For example, the opening or outlet can have at least one shape selected from the group consisting of circular, rectangular, elliptical, ring-like, triangular, polygonal, or any shape suitable for delivering gas into the cloud of evaporated material.

[0070] While the foregoing is directed to implementations of the disclosure, other and further implementations of the disclosure may be devised without departing from the basic scope of the disclosure, the scope of which is determined by the claims.

Claims

1. 1. A method of forming a separator for a battery, comprising: exposing a first material deposited on a microporous ion-conducting polymer layer disposed in a treatment area to an evaporation process, the microporous ion-conducting polymer layer being: A first surface; A second surface opposite the first surface; and a first ceramic-containing layer capable of conducting ions formed on the first surface, the first ceramic-containing layer being prepared by a slot-die technique or a doctor blade technique and having a thickness in the range of 1,000 nanometers to 5,000 nanometers; exposing, reacting the evaporated first material with a reactive gas and / or plasma to deposit a second ceramic-containing layer capable of conducting ions on a second surface of the microporous ion-conducting polymer layer, the second ceramic-containing layer comprising aluminum oxide and / or lithium aluminum oxide, a binder-free ceramic-containing layer, and having a thickness in the range of 1 nanometer to 1,000 nanometers; and then reacting the evaporated second material with a second reactive gas and / or plasma to deposit a third ceramic-containing layer capable of conducting ions on the second ceramic-containing layer. Including, The method, wherein the third ceramic-containing layer is binder-free and has a thickness in the range of 1 nanometer to 100 nanometers.

2. The first ceramic-containing layer is: porous aluminum oxide, porous ZrO 2 , porous HfO 2 , porous SiO 2 , porous MgO, porous TiO 2 , porous Ta 2 O 5 , porous Nb 2 O 5 , porous LiAlO 2 , porous BaTiO 3 , ionically conductive garnets, anti-ionically conductive perovskites, porous glass dielectrics, or combinations thereof.

3. The method of claim 1 , wherein the first ceramic-containing layer comprises a binder.

4. The method of claim 1 , wherein the first material to be deposited is a metallic material comprising aluminum.

5. The method of claim 1 , wherein the first material evaporated is a metal oxide comprising lithium aluminum oxide.

6. The method of claim 1 further comprising exposing the microporous ion-conducting polymer layer to a cooling process prior to exposing the first material to the evaporation process.

7. The method of claim 6, wherein the cooling process cools the microporous ion-conducting polymer layer to a temperature of from -20°C to 22°C.

Citation Information

Patent Citations

  • Separator, battery using the same, method of manufacturing the separator, fine porous membrane, and method of manufacturing the fine porous membrane

    JP2011113915A

  • Battery separator with dielectric coating

    JP2018523263A

  • Membranes, separators, batteries, and methods

    US20170025658A1